Effects of additives in reducing the odour concentration emanating from water scrubber in rubber processing factory / Mohd Ikram Mohammad... [et al.] - Mohammad, Mohd Ikram; Alias, Nor Azieda; Idris, Nur Fadhilah; Mustafa, Asrul (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
The paper describes the effects of additives incorporated into the scrubbing medium in reducing the odour concentration emanating from the water scrubber treatment system (WSTS) in Standard Malaysian Rubber (SMR) processing factory. Two different types of commercial WSTS additives were used in a lab scale simulation of a WSTS using water scrubber samples (WSS) as the scrubbing medium that were sourced from a local SMR processing factory. The WSS after incorporation of the additives were tested for odour concentration via olfactometry analysis. Total solid content, suspended solid, pH, UV-vis analysis and contact angle measurements of the WSS were also conducted. The results of olfactometry analysis indicated that each of the additives reduced the odour concentration level by 9.25% and 42.84%, respectively. The reduction in odour concentration was accompanied by an increase in total solid, suspended solid, pH and UV measureable compounds which may indicate an increase in the WSTS efficiency. The additions of additives were also shown to reduce the contact angle of the WSS that could plausibly be attributed to changes in the wetting properties of WSS. The work conducted has presented the likely effects of additives in the scrubbing medium or WSS of the WSTS in terms of its performance and properties.